Protective Immunity to Rotavirus Shedding in the Absence of Interleukin-6: Th1 Cells and Immunoglobulin A Develop Normally - VanCott, John L. (American Society for Microbiology, 2000)
We investigated whether interleukin-6 (IL-6) was required for the development of immunoglobulin A (IgA)- and T-helper 1 (Th1)-associated protective immune responses to rotavirus by using adult IL-6-deficient mice [BALB/c and (C57BL/6 × O1a)F(2) backgrounds]. Naive IL-6(−) mice had normal frequencies of IgA plasma cells in the gastrointestinal tract. Consistent with this, total levels of IgA in fecal extracts, saliva, and sera were unaltered. In specific response to oral infection with rhesus rotavirus, IL-6(−) and IL-6(+) mice exhibited efficient Th1-type gamma interferon responses in Peyer's patches with high levels of serum IgG2a and intestinal IgA. Although there was an increase in Th2-type IL-4 in CD4(+) T cells from IL-6(−) mice following restimulation with rotavirus antigen in the presence of irradiated antigen-presenting cells, unfractionated Peyer's patch cells failed to produce a significant increase in IL-4. Moreover, virus-specific IgG1 in serum was not significantly increased in IL-6(−) mice in comparison with IL-6(+) mice. Following oral inoculation with murine rotavirus, IL-6(−) and IL-6(+) mice mediated clearance of rotavirus and mounted a strong IgA response. When IL-6(−) and IL-6(+) mice [(C57BL/6 × O1a)F(2) background] were orally inoculated with rhesus rotavirus and later challenged with murine rotavirus, all of the mice maintained high levels of IgA in feces and were protected against reinfection. Thus, IL-6 failed to provide unique functions in the development of IgA-secreting B cells and in the establishment of Th1-associated protective immunity against rotavirus infection in adult mice.